KETERLIBATAN PENGASUHAN AYAH SEBAGAI ORANG TUA TUNGGAL DENGAN ANAK PEREMPUANNYA SETELAH TERJADINYA PERCERAIAN (STUDI KASUS KOMUNIKASI ANTARPRIBADI DI DESA KWANGSAN, KECAMATAN JUMAPOLO) - Astuti, Denny (Universitas Muhammadiyah Surakarta, 2016)
Being a single parent is not easy especially for father, and caring for his girls are still?under age of 12 years old. Beside for suffice the needs of the family of an themselves a?father is a single parent should parenting is independent. The purpose of the research to?describe how to engagement parenting father as a single parent to his daughter after the?occurance of divorce. This research using descriptive qualitative method with the approach?of communication interpersonal. The object of this research consist of three father became a?single parent because of the background of divorce in Jumapolo subdistrict. The technique?of collecting data using semi-structured interview. The method of analysing data usingdescriptive analysing. The result of this research suggests that: (1) the communication?interpersonal conducted father as a single parent to this child to give understanding of the?family is not explained about divorce but give understanding of the work of this mother, (2)?engagement parenting conducted in independent and not involved to the other, (3) the?responsibility of father when leaving the girls with entrusting to this family, (4) accessibility?is a single parent, father always give time to accompany for playing and activities his child?everyday. It can be concluded that the involvement parenting father as a single parent to his?daughter is directly in all fulfillment needs.